Penguatan Literasi Hak Asasi Manusia (HAM) guna Mewujudkan Generasi Sadar Hukum bagi Pelajar SMA Negeri 1 Boja - Aryaputra, Muhammad Iftar; Septiandani, Dian; Izziyana, Wafda Vivid (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2025)
1st Boja Senior High School is one of the schools that declares itself to be “sekolah ramah anak”. With "ramah anak" status, 1st Boja Senior High School aims to create a safe, comfortable, and conducive environment for teaching and learning activities. Respect for other people's human rights contributes to forming an academic climate in schools that is friendly to children. Based on a survey conducted previously, there are still many practices occurring in 1st Boja Senior High School, human rights violations committed by students, in the form of bullying, especially verbal bullying. This legal counseling correlates and is a form of support for schools that have the status of "sekolah ramah anak.". It is hoped that providing human rights literacy can provide students with an understanding of the importance of respecting human rights so that they can eliminate forms of bullying in their environment. The method used is carried out in three stages, namely pre-activity, activity, and post-activity. After giving a lecture on human rights, the students increasingly understood the importance of respect for other people. Students already understand the concept of respecting other people's rights. Still, with this counseling, students will better understand human rights law, where it is very important to respect other people's rights.   Keywords: Literacy; Human Rights; Law Awareness;